Biblioshiny Application to Map Halal Logistic Research - Rahardjo, Sri (SMART Insight, 2023)
This study aims to observe the development of halal logistics topics through the analysis of scientific literature registered in the Scopus database during the period 2007-2023 using the bibliometric method. The research method used is biblioshiny-R. The results showed that the number of publications on halal logistics fluctuated and showed an increasing trend, reaching its peak in 2023 with a total of 36 documents. Malaysia leads in author participation, reaching 417 documents. The average citation analysis highlighted 2011 as the period with the highest average citation, which is about 7.5 citations per year.